Focusing on neglected zoonoses - Doble, L.; Fèvre, Eric M. (Wiley, 2010)
Two tenets at the core of the One Health concept are the belief that human and animal health are irrevocably entwined and that the improvement of both requires close collaboration between the medical and veterinary professions with support from allied disciplines. An ongoing Wellcome Trust‐supported project in Western Kenya – the ‘People, Animals and their Zoonoses’ (PAZ) project – holds the One Health theme at its centre as it endeavours to study neglected zoonoses and provide policy‐relevant information about their epidemiology. Veterinarian Lian Doble and the project’s leader Eric Fèvre explain why this study is so important.